A New Smoothing Equations Approach to the Nonlinear Complementarity Problems (Journal of Computational Mathematics, 2021)
The nonlinear complementarity problem can be reformulated as a nonsmooth equation. In this paper we propose a new smoothing Newton algorithm for the solution of the nonlinear complementarity problem by construction a new smoothing approximation function. Global and local superlinear convergence results of the algorithm are obtained under suitable conditions. Numerical experiments confirm the good theoretical properties of the algorithm.
Keywords: Nonlinear complementarity problem; Smoothing Newton method; Global convergence; Superlinear convergence.